Qatar's foreign policy : decision-making processes, baselines, and strategies - Steinberg, Guido (2023)
Zusammenfassung: Qatar's domestic and foreign policy since the 1990s has developed along three main lines: The emirate has expanded its gas production and supplies liquefied gas to as many countries as possible; it assures itself of US military protection by providing bases; and it conducts a "soft power" campaign in the form of investments in media and sports. During the Arab Spring, Qatar went on the offensive, marking a change in its regional policy. At the time, it aimed at nothing less than revising the regional order in the Arab world. Since Emir Tamim took office in 2013, however, Doha has scaled back its ambitions, yet it still wants to be recognised as a regional power. Qatar tries to defuse regional conflicts by positioning itself as a mediator. It maintains good relations with Iran, its allies in the region and with militant groups such as Hamas and the Taliban. This, as well as its support for the Muslim Brotherhood, repeatedly provokes conflicts with Saudi Arabia and other neighbours. As a result, Qatar has identified Turkey as its new protecting power. Qatar is an attractive partner for Germany and Europe and can become an important gas supplier that has shown a long-standing interest in the European market; it is also more flexible in its deliveries than many of its competitors. It was a serious mistake for German policy not to focus on Qatari gas much earlier. Placing more long-term orders could rectify this mistake. If there really is going to be a "Zeitenwende" security policy, Germany must also prepare itself for security risks emanating from the Middle East (keywords: migration, terrorism, nuclear proliferation). This means that Germany and Europe need pro-Western allies like Qatar